DO CORRUPTION, FINANCIAL DEEPENING, AND INFLATION DRIVE ECONOMIC GROWTH IN SUMATRA? - Ratu Eva Febriani; Nauval Zaky Filloza; Retno Agustina Ekaputri; Esti Pasaribu (Universitas Tidar, 2023)
This study investigates whether the effect of corruption, financial deepening, and inflation on economic growth exists employing panel regression of 10 provinces on the island of Sumatra over the period 2012-2020. Using the fixed effect model as the best model, the results confirm that between corruption, financial deepening, inflation and economic growth, a simultan relationship exists. Moreover, the FEM panel regression estimations indicate that corruption does not significantly affect economic growth, whereas financial deepening and inflation positively affect economic growth. The policy implication is that, for every province in Sumatra Island, boosting financial deepening and inflation can help promote economic growth. The policy effects are related to the prosperity of different regions.